Acquired knowledge of pharmacy students regarding the rational use of antibiotics through the curricula of the faculty - Milošević Georgiev, Andrijana; Krajnović, Dušanka; Petković, Marija; Jambrek, Jakov; Šesto, Sofija (Archives of Pharmacy, 2022)
Discovery of antibiotics significantly decreased the mortality rate and extended life expectancy. However, the irrational use of antibiotics has made bacteria resistant to a number of them. Many countries are adopting certain strategies for the use of the antibiotics. Integral parts of these strategies are the education of health professionals as well as KAP research (knowledge, attitudes and behaviors) of medical students regarding the rational use of antibiotics. The aim of the research was to examine the knowledge of pharmacy students regarding the rational use of antibiotics in Serbia through an online questionnaire. The research was conducted among 375 students, during 2019 at 5 faculties in Serbia with department of pharmacy from junior to senior study year. The sample was determined as 10% of the total number of students in each year of study. The average age of respondents was 22.15 ± 1.78 years. The largest percentage of students (86.9%) answered that a module on the rational use of antibiotics (drugs) within the Pharmacy study program is needed. Respondents' knowledge was tested through 15 questions. The total percentage of correct answers in the questionnaire was 85.2%. Most of the respondents had 14 correct answers (32%), while 16.8% had all 15. The knowledge level mostly grew from the first to the final year of study. The knowledge of Serbian pharmacy students regarding the rational use of antibiotics is at a high level and they are aware of the antimicrobial resistance problems as well as the irrational use of antibiotics.